PERANAN MINAT BELI ULANG DALAM MEMEDIASI PENGARUH BAURAN PEMASARAN, CITRA TOKO, LOKASI TERHADAP LOYALITAS KONSUMEN PADA TOKO DARUL FALAH CERMEE BONDOWOSO - Ersatul Ibad; Triska Dewi Pramitasari; Yudha Praja (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Toko Darul Falah is a retail store that offers a variety of daily necessities, primarily catering to the needs of male and female students (santri and santriwati) at Islamic boarding schools (pesantren). Over time, however, the store has expanded to serve the general public, capitalizing on promising market potential in the surrounding area. This study aims to examine the effect of the marketing mix, store image, and location on customer loyalty, with repurchase intention as an intervening variable at Toko Darul Falah Cermee Bondowoso. The population in this study consists of 6,880 customers, with a sample size of 99 respondents selected using simple random sampling. Data analysis and hypothesis testing were conducted using SmartPLS 3.0. The results of direct effect hypothesis testing indicate that both the marketing mix and store image have a significant effect on repurchase intention and customer loyalty. Location has a significant impact on repurchase intention, but does not significantly influence customer loyalty. Furthermore, repurchase intention does not have a significant effect on customer loyalty.